Comparing open gastrostomy tube to percutaneous endoscopic gastrostomy tube in heart transplant patients. (May 2016) - Ambur, Vishnu; Taghavi, Sharven; Jayarajan, Senthil; Gaughan, John; Toyoda, Yoshiya; Dauer, Elizabeth; Sjoholm, Lars Ola; Pathak, Abhijit; Santora, Thomas; Goldberg, Amy J.
Abstract: Introduction: Impaired wound healing due to immunosuppression has led some surgeons to preferentially use open gastrostomy tube (OGT) over percutaneous gastrostomy tube (PEG) in heart transplant patients when long-term enteral access is deemed necessary. Methods: The National Inpatient Sample (NIS) database (2005–2010) was queried for all heart transplant patients. Those receiving OGT were compared to those treated with PEG tube. Results: There were 498 patients requiring long-term enteral access treated with a gastrostomy tube, with 424 (85.2%) receiving a PEG and 74 (14.8%) an OGT. The PEG cohort had higher Charlson comorbidity Index (4.1 vs. 2.0, p = 0.002) and a higher incidence of post-operative acute renal failure (31.5 vs. 12.7%, p = 0.001). Post-operative mortality was not different when comparing the two groups (13.8 vs. 6.1%, p = 0.06). On multivariate analysis, while both PEG (OR: 7.87, 95%C.I: 5.88–10.52, p < 0.001) and OGT (OR 5.87, 95%CI: 2.19–15.75, p < 0.001) were independently associated with mortality, PEG conferred a higher mortality risk. Conclusions: This is the largest reported study to date comparing outcomes between PEG and OGT in heart transplant patients. PEG does not confer any advantage over OGT in this patient population with respect to morbidity, mortality, and length of stay. Highlights: OGT may result in less mortality than PEG in heart transplant patients. Complications occur more frequently when heart transplant recipients receive PEG. PEG in heart transplant recipients does not result in decreased LOS or total cost.